A Case Series of alpha-Thalassemia Intermedia Due to Compound Heterozygosity for Hb Adana [HBA2: c179G > A (or HBA1); p.Gly60Asp] With Other alpha-Thalassemias in Malay Families - Alauddin, H; Jaapar, NA; Azma, RZ; Ithnin, A; Razak, NFA; Loh, CK; Alias, H; Abdul-Latiff, Z; Othman, A (Taylor & Francis Ltd, 2024)
Indexed by WOS/Scopus